Epidemiology and Treatment of Patients with Haemophilia in Austria—Update from the Austrian Haemophilia Registry - Rejtő, Judit; Reitter-Pfoertner, Sylvia; Kepa, Sylvia; Feistritzer, Clemens; Grundbichler, Michael; Hörbst, Alexander; Jones, Neil; Muntean, Wolfgang; Neumeister, Peter; Oberbichler, Stefan; Schuster, Gerhard; Schwarz, Rudolf; Thom, Katharina; Zwiauer, Karl; Streif, Werner; Male, Christoph; Pabinger, Ingrid (Hämostaseologie, 2019)
The Austrian Haemophilia Registry collects epidemiological data on patients with haemophilia, on treatment modalities and potential side effects. The Registry covers more than 85% of the assumed total number of haemophilia patients in Austria. This report summarizes data on 753 patients: 84.3% (635) have haemophilia A and 15.7% (118) have haemophilia B. Patients' median age is 34 years (range: 1–93 years). Of the total cohort, 39.0% (294) patients have severe haemophilia, 11.3% (85) moderate haemophilia, and 49.4% (372) mild haemophilia. Of the patients with severe haemophilia, 38.4% (113) have been infected with hepatitis C virus (HCV) and 12.6% (37) are human immunodeficiency virus (HIV) positive. Overall, 10.6% (67) of patients with haemophilia A and 1.7% (2) of those with haemophilia B have had an inhibitor in their history. Among patients with severe haemophilia, 68.4% (201) receive prophylaxis and 28.6% (84) receive on-demand therapy. There are 65.0% (191) patients with severe haemophilia who are treated with recombinant products. In conclusion, most patients with severe haemophilia receive prophylactic treatment. HCV and HIV infections are still important issues in the Austrian haemophilia population.
Keywords: Austrian Haemophilia Registry; hepatitis C virus; congenital bleeding disorder